PERBANDINGAN METODE LATIHAN PIRAMID NORMAL DAN TERBALIK TERHADAP PENINGKATAN HIPERTROFI OTOT LENGAN DAN PAHA - Sandra Arhesa; Rudi Rudi (Universitas Majalengka, 2019)
Sandra Arhesa dan Rudi Prodi Pendidikan Jasmani, Universitas Majalengka arhesasandra@unma.ac.id ABSTRACT This study aimed to determine the comparison between the pyramid and reverse pyramid training methods to increase arm and thigh muscle hypertrophy. This study used an experimental research method, the research design used was a pretest-posttest design, with a population of all members of BP Bumi Sangkuriang Fitness Center totaling 50 people. The sampling technique uses purvosive sampling techniques. So the sample taken was 20 people, 10 people used the pyramid training method and 10 people used the reverse pyramid training method. Instruments are meters, standing dumbell curls and leg extensions. Data Analysis Techniques by testing the mean and standard deviation, normality, homogeneity and hypothesis. The results of the analysis in this study indicate an influence on the increase in muscle hypertrophy using the pyramid and inverted pyramid training methods and there is a significant comparison between the pyramid and inverted pyramid training methods to increase muscle hypertrophy, especially the arm and thigh muscles, with improved muscle hypertrophy using Pyramid training method. It is expected that in the future research will be carried out to increase hypertrophy with the method of pyramid training and inverted pyramids on other types of muscle and more than one month of research with more samples. Keywords: Muscle Hypertrophy, Weight Training, Exercise Method, Pyramid System and Reverse Pyramid